Evaluation and update of the expert consensus guidelines for the assessment of the cortisol awakening response (CAR). (December 2022) - Stalder, Tobias; Lupien, Sonia J.; Kudielka, Brigitte M.; Adam, Emma K.; Pruessner, Jens C.; Wüst, Stefan; Dockray, Samantha; Smyth, Nina; Evans, Phil; Kirschbaum, Clemens; Miller, Robert; Wetherell, Mark A.; et al.
Summary: The cortisol awakening response (CAR) is frequently assessed in psychobiological (stress) research. Obtaining reliable CAR data, however, requires careful attention to methodological detail. To promote best practice, expert consensus guidelines on the assessment of the CAR were published (Stalder et al., 2016, PNEC ). However, it is unclear whether these highly cited guidelines have resulted in actual methodological improvements. To explore this, the PNEC editorial board invited the present authors to conduct a critical evaluation and update of current CAR methodology, which is reported here. (i) A quantitative evaluation of methodological quality of CAR research published in PNEC before and after the guidelines (2013–2015 vs. 2018–2020) was conducted. Disappointingly, results reveal little improvement in the implementation of central recommendations (especially objective time verification) in recent research. (ii) To enable an update of guidelines, evidence on recent developments in CAR assessment is reviewed, which mostly confirms the accuracy of the majority of the original guidelines. Moreover, recent technological advances, particularly regarding methods for the verification of awakening and sampling times, have emerged and may help to reduce costs in future research. (iii) To aid researchers and increase accessibility, an updated and streamlined version of the CAR consensus guidelines is presented. (iv) Finally, the response of the PNEC editorial board to the present results is described: potential authors of future CAR research to be published in PNEC will be required to submit a methodological checklist (based on the current guidelines) alongside their article. This will increase transparency and enable reviewers to readily assess the quality of the respective CAR data. Combined, it is hoped that these steps will assist researchers and reviewers in assuring higher quality CAR assessments in future research, thus yielding more reliable and reproducible results and helping to further advance this field of study. Highlights: CAR assessment guidelines published in 2016, but unknown if followed by research. Quantitative evaluation results: Main guidelines are still not consistently followed. Evidence of recent developments in CAR methodology is reviewed. Updated CAR consensus guidelines are presented. Future CAR submissions to PNEC have to fill in checklist based on guidelines.